Analisis Strategi Pemberdayaan Masyarakat dalam Program Kampung Nanas di Kalurahan Margoluwih, Seyegan, Sleman: Penelitian - Jihani Nurseha; Siti Nurlaela; Agus Wartapa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Community empowerment is a strategic effort to increase the independence and welfare of residents through the utilization of local potential. This empowerment through the Kampung Nanas program focuses on the cultivation of Smooth Cayenne pineapple varieties. However, the empowerment approach taken has not been optimal. This study aims to analyze the factors that influence the community empowerment process and formulate strategies that can be applied in Margoluwih Village. The research approach uses a qualitative method with case studies, involving observation, interviews, and Focus Group Discussions (FGD). The analysis used is SWOT and QSPM. The results of the study indicate that technical training on good and correct pineapple cultivation, as well as providing access for the community to consult with experts in the field, plays an important role in improving the quality of pineapple cultivation. This effort is expected to produce optimal pineapple plants. In addition, ongoing assistance and regular meetings have proven to be effective strategies in empowering communities in Margoluwih Village. This study confirms that an empowerment strategy based on a participatory model, with financial support from the government and the involvement of millennial farmers as assistants, can increase the sustainability of community empowerment programs through the Kampung Nanas program. Therefore, village governments and agricultural extension workers need to design collaborations to increase community income in a sustainable manner.